The Memory-Enhancing Effects of Liquiritigenin by Activation of NMDA Receptors and the CREB Signaling Pathway in Mice - Ko, Yong-Hyun (Biomol Ther (Seoul), 2018)
Liquiritigenin (LQ) is a flavonoid that can be isolated from Glycyrrhiza radix. It is frequently used as a tranditional oriental medicine herbal treatment for swelling and injury and for detoxification. However, the effects of LQ on cognitive function have not been fully explored. In this study, we evaluated the memory-enhancing effects of LQ and the underlying mechanisms with a focus on the N-methyl-D-aspartic acid receptor (NMDAR) in mice. Learning and memory ability were evaluated with the Y-maze and passive avoidance tests following administration of LQ. In addition, the expression of NMDAR subunits 1, 2A, and 2B; postsynaptic density-95 (PSD-95); phosphorylation of Ca(2+)/calmodulin-dependent protein kinase II (CaMKII); phosphorylation of extracellular signal-regulated kinase 1/2 (ERK 1/2); and phosphorylation of cAMP response element binding (CREB) proteins were examined by Western blot. In vivo, we found that treatment with LQ significantly improved memory performance in both behavioral tests. In vitro, LQ significantly increased NMDARs in the hippocampus. Furthermore, LQ significantly increased PSD-95 expression as well as CaMKII, ERK, and CREB phosphorylation in the hippocampus. Taken together, our results suggest that LQ has cognition enhancing activities and that these effects are mediated, in part, by activation of the NMDAR and CREB signaling pathways.